Demonstrating the Impact of Cognitive CEO on Firms’ Performance and CSR Activity - Li, Hui; Hang, Yong; Shah, Syed Ghulam Meran; Akram, Aswad; Ozturk, Ilknur (Frontiers in Psychology, 2020)
One aspect of entrepreneurship psychology also clarifies individual characteristics. Drawing from entrepreneurship psychology, the concept of a cognitive CEO has been formulated using the DAE statistical technique. The study elucidates that cognitive CEOs not only boost SME performance but also invigorate CSR activity. Data for listed SMEs for the years 2016–2018 are analyzed through the panel regression technique. Significantly, the study demonstrates that CEO age is positively interlinked with the growth and CSR activity of the firm. Moreover, the empirical underpinning of the results also reveals that state-owned enterprises and firms with high total assets prefer cognitive CEOs, who accelerate the firm’s value and invigorate CSR activity. The number of independent directors is analyzed as a moderator and is concluded to be an intensifier for both SME growth and CSR activity. Finally, 2SLS instrumental panel regression is used to validate the veracity of the empirical results.